INTERNET OF THINGS (IoT) SEBAGAI PILAR KEAMANAN DATA PADA SISTEM DISTRIBUSI DI INDONESIA - Mut'Mainna Mut'Mainna; Andi Muhammad Rivai; Andhi Febisatria; Titi Sarnawiyah; Muhammad Rafli Setiawan (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The Internet of Things (IoT) is an advanced technology that integrates physical objects with the internet through sensors, facilitating intellectual interaction between devices and providing increased efficiency and control in various dimensions of life and business activities. In Indonesia, the implementation of IoT has experienced significant expansion, particularly in the industrial distribution sector, although this poses substantial challenges related to data security. This study aims to explore the role of IoT as the foundation of data security in industrial distribution systems in Indonesia. The methodology applied involves a literature review of scientific journals, industry reports, and recent reliable articles. The findings indicate that IoT contributes to data security through encryption, authentication, intrusion detection, and anomaly detection systems that improve the accuracy of cyber threat identification. In addition, IoT can reduce human error, maintain product quality standards, and strengthen data integrity throughout the distribution chain. However, its effectiveness depends on technical, organizational, and regulatory factors that require further strengthening to ensure sustainable security.